Imitation-mussel fluorescent silicon quantum dots for selective labeling and imaging of bacteria and biofilms - Lin, Jiayi; Xu, Linlin; Zheng, Yuling; Wu, Dalin; Yue, Jun (Frontiers in Bioengineering and Biotechnology, 2022)
Selective labeling of distinct bacteria and biofilm is poised for the fundamental understanding of bacterial activities, interactions, and coupled phenomena occurring at the microscale. However, a simple and effective way to achieve selective bacterial labeling is still lacking. Herein, we report a fluorescence probe with core-shell nanostructure that has polydopamine (PDA) coating on the surface of fluorescent silicon quantum dots (SiQDs@PDA). The surface of the SiQDs@PDA can be functionalized by various molecules (2-mercaptoethylamine hydrochloride, PEG, d-alanine, glucose amide) through different strategies (Michael addition, π-π interaction, and ion–ion interaction). Importantly, the d-alanine (D-Ala)- and gluconamide (Glc)-functionalized SiQDs@PDA fluorescence probes are capable of selectively labeling gram-positive and gram-negative bacteria, as well as their biofilms. The excellent performance in universal functionalization and selective labeling and imaging of bacteria and their biofilms demonstrate that SiQDs@PDA are a promising fluorescence tool in microbe research.